Experience of Contraception Drop Out in Women of Reliable Age - Bella Riska Ayu; Ismarwati; Mamnu’ah (Jurnal Health Sains, 2022)
Contraceptive drop out is a public health problem that has a negative effect on women's reproductive health outcomes. A high proportion of contraceptive dropouts without a woman's desire to become pregnant is associated with unwanted pregnancies, unwanted births and unsafe abortions. This scoping review aims to map the literature, identify knowledge gaps and examine scientific evidence regarding the experience of contraceptive drop out in women of childbearing age (WUS). This scoping review method uses the Arksey and O'Malley framework, which starts from identifying scoping review questions using the PEOS framework; identify relevant articles; search for articles using relevant databases namely PubMed, ScienceDirect, EBSCO, Wiley, and Google Scholar; the flow of the article search process is explained through the PRISMA flowchart; perform critical appraisals; perform data charting; compiling, summarizing and reporting results. The results, based on 21 selected articles, obtained 19 articles with grade A and 2 articles grade B. Three themes were found in this scoping review, namely perceptions of family planning, factors causing family planning drop out, and obstacles. It can be concluded that the low level of information dissemination and education related to contraception from health workers can be one of the causes of the low level of awareness and knowledge of WUS regarding contraception, as well as the existence of obstacles in contraceptive services that can be a barrier in reducing contraceptive drop out rates in various countries.